Current Evidence of Interleukin-6 Signaling Inhibitors in Patients With COVID-19: A Systematic Review and Meta-Analysis - Han, Qi; Guo, Mingyue; Zheng, Yue; Zhang, Ying; De, Yanshan; Xu, Changchang; Zhang, Lin; Sun, Ruru; Lv, Ying; Liang, Yan; Xu, Feng; Pang, Jiaojiao; et al. (Frontiers in Pharmacology, 2020)
Background Interleukin-6 (IL-6) is known to be detrimental in Coronavirus Disease 2019 (Covid-19) because of its involvement in driving cytokine storm. This systematic review and meta-analysis aimed to assess the safety and efficacy of anti-IL-6 signaling (anti-IL6/IL-6R/JAK) agents on Covid-19 based on current evidence. Methods Studies were identified through systematic searches of PubMed, EMBASE, ISI Web of Science, Cochrane library, ongoing clinical trial registries (clinicaltrials.gov), and preprint servers (medRxiv, ChinaXiv) on 10 August 2020, as well as eligibility checks according to predefined selection criteria. Statistical analysis was performed using Review Manager (version 5.3) and STATA 12.0. Results Thirty-one studies were included in the pooled analysis of mortality, and 12 studies were identified for the analysis of risk of secondary infections. For mortality analysis, 5630 Covid-19 cases including 2132 treated patients and 3498 controls were involved. Anti-IL-6 signaling agents plus standard of care (SOC) significantly decreased the mortality rate compared to SOC alone (pooled OR = 0.61, 95% CI 0.45–0.84, P = 0.002). For the analysis of secondary infection risk, 1624 patients with Covid-19 including 639 treated patients and 985 controls were included, showing that anti-IL-6 signaling agents did not increase the rate of secondary infections (pooled OR = 1.21, 95% CI 0.70–2.08, P = 0.50). By contrast, for patients with critical Covid-19 disease, anti-IL-6 signaling agents failed to reduce mortality compared to SOC alone (pooled OR = 0.75, 95% CI 0.42–1.33, P = 0.33), but they tended to increase the risk of secondary infections (pooled OR = 1.85, 95% CI 0.95–3.61, P = 0.07). Blockade of IL-6 signaling failed to reduce the mechanical ventilation rate, ICU admission rate, or elevate the clinical improvement rate. Conclusion IL-6 signaling inhibitors reduced the mortality rate without increasing secondary infections in patients with Covid-19 based on current studies. For patients with critical disease, IL-6 signaling inhibitors did not show benefit.